2001
DOI: 10.1016/s0022-1694(00)00403-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term rise in a Sahelian water-table: the Continental Terminal in South-West Niger

Abstract: The Continental Terminal water-table near Niamey (S-W Niger) has been the subject of a dense and detailed survey conducted over a period of almost 15 yr. The continuous rise in the groundwater level was unexpected but manifest and varied between 0.01 and 0.45 m yr-'. As shown by corroborating measurements made throughout the twentieth century, this rise has been taking place for much longer and present levels are the highest ever recorded. Since the beginning of the 1960s, groundwater resources have increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
129
0
12

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(176 citation statements)
references
References 13 publications
7
129
0
12
Order By: Relevance
“…During the same dry years the phenomenon know as "Sahelian paradox" (Descroix et al, 2009) was observed in many part of the Sahel: an increase in runoff despite the deficit in rainfall (Albergel, 1987;Amani and Nguetora, 2002;Mahé et al, 2003Mahé et al, , 2005Mahé and Paturel, 2009). This phenomenon resulted from a discharge increase in exorheic 1 basins (Amani and Nguetora, 2002;Mahé et al, 2003Mahé et al, , 2005Mahé and Paturel, 2009;Descroix et al, 2009;Amogu et al, 2010) and in larger pond surfaces, infiltration and water table levels in the endorheic 2 areas (Desconnet et al, 1997;Leduc et al, 2001;Gardelle et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…During the same dry years the phenomenon know as "Sahelian paradox" (Descroix et al, 2009) was observed in many part of the Sahel: an increase in runoff despite the deficit in rainfall (Albergel, 1987;Amani and Nguetora, 2002;Mahé et al, 2003Mahé et al, , 2005Mahé and Paturel, 2009). This phenomenon resulted from a discharge increase in exorheic 1 basins (Amani and Nguetora, 2002;Mahé et al, 2003Mahé et al, , 2005Mahé and Paturel, 2009;Descroix et al, 2009;Amogu et al, 2010) and in larger pond surfaces, infiltration and water table levels in the endorheic 2 areas (Desconnet et al, 1997;Leduc et al, 2001;Gardelle et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, in some part of the Sahel, the rainfall deficit did not lead to a decrease in surface runoff or in water-table level, as it happened in the wetter Soudanian and Guinean zones further south in West Africa (Descroix et al, 2009). Indeed, evidence of an increase in water-table level has been reported in endorheic areas, such as in south-western Niger (Leduc et al, 2001). Along the same line, Mahé et al (2003Mahé et al ( , 2005a outlined changes in hydrologic regime of rivers located in Burkina Faso, Mali and Niger, showing a discharge increase north of the 700-mm isohyets, and therefore, over northern J.…”
Section: Introductionmentioning
confidence: 78%
“…The density and canopy cover of woody populations are low in average (Hiernaux et al, 2009b). However, there are concentrations of woody plants along drainage lines, around ponds, in the inter-dune depressions and also on shallow soils, with a regular pattern of narrow linear thickets set perpendicular to the slope known as "tiger bush" (Leprun, 1992;Hiernaux and Gerard, 1999). These thickets live on the water and nutrients harvested on the impluvium made by the bare soil upstream, and their development efficiently limit runoff further downstream (d'Herbes et al, 1997).…”
Section: The Study Sitementioning
confidence: 99%
“…Pressure on grazing resources from cultivation is particularly a problem in the southern Sahel where seasonal, long-distance livestock movements to the north during the rainy season (e.g., transhumance) have been historically important. Interestingly, a "re-greening" of the Sahel has been observed over the past 30 years from satellite images (Olsson et al 2005) and verified by field work (Dardel et al 2014) where rainfall and net primary productivity have increased, and this mitigates some otherwise negative trends (Gardelle et al 2010;Hiernaux et al 2009, Leduc et al 2001. Vegetation change in the Sahel appears to be more influenced by precipitation than livestock effects and thus is an example of nonequilibrium dynamics (Ellis and Swift 1988) 23,24 .…”
Section: Trends In Resource Use and Ecological Condition Of Rangelandsmentioning
confidence: 84%